Sequencing platform shifts provide opportunities but pose challenges for combining genomic data sets. (23rd December 2020) - De‐Kayne, Rishi; Frei, David; Greenway, Ryan; Mendes, Sofia L.; Retel, Cas; Feulner, Philine G. D.
Abstract: Technological advances in DNA sequencing over the last decade now permit the production and curation of large genomic data sets in an increasing number of nonmodel species. Additionally, these new data provide the opportunity for combining data sets, resulting in larger studies with a broader taxonomic range. Whilst the development of new sequencing platforms has been beneficial, resulting in a higher throughput of data at a lower per‐base cost, shifts in sequencing technology can also pose challenges for those wishing to combine new sequencing data with data sequenced on older platforms. Here, we outline the types of studies where the use of curated data might be beneficial, and highlight potential biases that might be introduced by combining data from different sequencing platforms. As an example of the challenges associated with combining data across sequencing platforms, we focus on the impact of the shift in Illumina's base calling technology from a four‐channel system to a two‐channel system. We caution that when data are combined from these two systems, erroneous guanine base calls that result from the two‐channel chemistry can make their way through a bioinformatic pipeline, eventually leading to inaccurate and potentially misleading conclusions. We also suggest solutions for dealing with such potential artefacts, which make samples sequenced on different sequencing platforms appear more differentiated from one another than they really are. Finally, we stress the importance of archiving tissue samples and the associated sequences for the continued reproducibility and reusability of sequencing data in the face of ever‐changing sequencing platform technology.